Students’ Attitude Towards Media Of Learning Based On Artificial Intelligence (Ai): Smodin On Teacher Training Faculty Of Universitas HKBP Nommensen Pematangsiantar - Ieonita Maria Efipanias Manihuruk; Yanti Arasi Sidabutar; Leta Rumahorbo (CV Putra Publisher, 2026)
Technology has become a major 21st -century keyword in teaching and learning in all level of education. With the booming demand for integrated technology into education has brought a new shifting paradigm to be more effective and efficient way of learning a foreign language particularly English. Integrating technology into teaching and learning process has created new trends and impact on students’ learning atmosphere. Learning media is anything that can efficiently and effectively channel messages from a source and provide a favorable learning environment for the recipient to carry out the learning process. One of the promising products of technology is artificial intelligence (AI). According to Dodigovic, (2007), artificial intelligence is an intelligent computerized machine can create a dialogue between human and machine in a natural way situation. Furthermore, Jia, (2009) stated that artificial intelligence can diagnose some typical errors in foreign language learning such as writing. Artificial Intelligence in education has introduced new models of pedagogy in English language learning. This research attempts to examine the attitudes of students on the use of artificial intelligence SMODIN in English language learning. This research aims to find out the students' attitudes towards media of learning based on AI. The research design of this research is a quantitative approach with a descriptive study design. The objective of this research is to find out how the students’ attitude towards media of learning based on the Artificial Intelligence (AI): SMODIN on Teacher Training Faculty of Universitas HKBP Nommensen Pematangsiantar and to find out the effect of SMODIN application on students’ English learning This research will published in Sinta 4 journal.